A genetic variant in toll‐like receptor 5 is linked to chemokine levels and hepatocellular carcinoma in steatohepatitis. (27th June 2021) - Nischalke, Hans Dieter; Fischer, Janett; Klüners, Alexandra; Matz‐Soja, Madlen; Krämer, Benjamin; Langhans, Bettina; Goeser, Felix; Soyka, Michael; Stickel, Felix; Spengler, Ulrich; Nattermann, Jacob; Strassburg, Christian P.; et al.
Abstract: Background & Aims: Bacterial translocation drives liver disease progression. We investigated whether functional genetic variants in toll‐like receptor 5 (TLR5), the receptor for bacterial flagellin, affect the risk for hepatocellular carcinoma (HCC). Methods: Healthy controls (n = 212), patients with alcohol abuse without liver disease (n = 382), and patients from a discovery cohort of alcohol‐associated cirrhosis (n = 372 including 79 HCC cases), a validation cohort of alcohol‐associated cirrhosis (n = 355 including 132 HCC cases), and a cohort of cirrhosis due to nonalcoholic steatohepatitis (NASH) (n = 145 including 62 HCC cases) were genotyped for the TLR5 rs5744174 and rs5744168 polymorphisms. Chemokine levels were measured by ELISA in patients' sera and supernatants of flagellin‐stimulated healthy monocytes. Results: Frequency of the TLR5 rs5744174 TT genotype was similar in healthy controls (33%), controls with alcohol abuse (34%), and patients with alcohol‐associated cirrhosis in the discovery (28%), validation (33%), and NASH cohort (31%). The TT genotype was enriched in patients with versus without HCC in the discovery, validation, and NASH cohort (41% vs 25%; 39% vs 29%; 40% vs 24%; p  < .05 each). This genotype remained a risk factor for HCC (OR = 1.9; p  = .01) after multivariate correction for age, gender, diabetes, and carriage of the PNPLA3 148M variant. Interleukin‐8 induction in monocytes from healthy controls and serum levels of interleukin‐8 and CXCL1 from cirrhotic patients with the TT genotype were significantly increased versus C allele carriers. Conclusion: The TLR5 rs5744174 polymorphism, affecting immune response to flagellin, is linked to occurrence of HCC in cirrhosis caused by steatohepatitis.